Role of BAF60a/BAF60c in chromatin remodeling and hepatic lipid metabolism. Issue 1 (December 2016) - Zhang, Ping; Li, Lulu; Bao, Zhengxi; Huang, Feiruo
Abstract The switching defective/sucrose non-fermenting (SWI/SNF) complexes play an important role in hepatic lipid metabolism regulating both transcriptional activation and repression. BAF60a is a core subunit of the SWI/SNF chromatin-remodeling complexes that activates the transcription of fatty acid oxidation genes during fasting/glucagon. BAF60c, another subunit of SWI/SNF complexes, is recruited to form the lipoBAF complex that activates lipogenic genes, promoting lipogenesis and increasing the triglyceride level in response to feeding/insulin. Interestingly, hepatocytes located in the periportal and perivenous zones of the liver display a remarkable heterogeneity in the activity of various enzymes, metabolic functions and gene expression. Especially, fatty-acid oxidation was shown to be mostly periportal, whereas lipogenesis was mostly perivenous. Therefore, the present review highlights the role of of SWI/SNF regulating lipid metabolism under nutritional and hormonal control, which may be associated with hepatocyte heterogeneity.